Cryopreserved Cadaveric Arterial Allograft for Arterial Reconstruction in Patients with Prosthetic Infection. (November 2017) - Lejay, Anne; Delay, Charline; Girsowicz, Elie; Chenesseau, Bettina; Bonnin, Emilie; Ghariani, Mohamed-Zied; Thaveau, Fabien; Georg, Yannick; Geny, Bernard; Chakfe, Nabil
Abstract : Objective: The aim of this study was to report outcomes of cryopreserved arterial allografts used as a vascular substitute in the setting of prosthetic material infection. Methods: A retrospective analysis of prospectively collected data was conducted including all consecutive interventions performed with cryopreserved arterial allografts used for vascular reconstruction in the setting of prosthetic material infection between January 2005 and December 2014. Five year outcomes included allograft related re-interventions, survival, primary patency, and limb salvage rates. Results: Fifty-three procedures were performed using cryopreserved allografts for vascular prosthetic infection: 25 procedures (47%) were performed at aorto-iliac level (Group 1) and 28 procedures (53%) at peripheral level (Group 2). The mean follow-up was 52 months. Five year allograft related re-intervention was 55% in Group 1 (6 allograft ruptures and 5 allograft aneurysm degenerations) and 33% in Group 2 (2 allograft ruptures and 7 allograft aneurysm degenerations). Five year survival was 40% and 68%, primary patency was 89% and 59% and limb salvage was 100% and 89% for Group 1 and 2 respectively. Conclusion: Use of cryopreserved arterial allografts provides acceptable results but is tempered by suboptimal 5 year outcomes with high re-intervention rates.